Echanges d'espaces : Oeuvres du Fonds Régional d'Art Contemporain de Franche-Comté. - Musée Arlaud, Lausanne; Besson, Christian; Chavanne, Blandine; Dary, Anne; Schaefer, Patrick; Zutter, Jörg (Lausanne : Musée des Beaux-Arts, 1994)
Abramovic, Marina ; Adams, Dennis ; Berger, Ueli ; Boltanski, Christian ; Bourget, Marie ; Collyer, Robin ; Cuzin, Christophe ; Fischli & Weiss ; Gette, Paul-Armand ; Grauerholz, Angela ; Heinze, Volker ; Hilliard, John ; Jézéquel, Claire-Jeanne ; Joumard, Veronique ; Lafont, Suzanne ; Lafontaine, Marie-Jo ; Gac, Jean Le ; Levine, Les ; Mach, David ; Marcel, Didier ; Marguet, Gilles ; Caslin, Matthew Mc ; Milner, Judy ; Moser, Claudio ; Yan Pei-Ming ; Piffaretti, Bernard ; Raetz, Markus ; Reip, Hugues ; Semmes, Thomas SchütteBeverly ; Siem, Wiebke ; Sorin, Pierrick ; Wurm, Erwin
biografie
Echanges d'espaces : Oeuvres du Fonds Régional d'Art Contemporain de Franche-Comté, Musée Arlaud, Lausanne, du 17 décembre 1994 au 25 février 1995
Frans
boek